Efektivitas Disnaker Kota Medan Dalam Menyelesaikan Permasalahan Sengketa Tenaga Kerja The Effectiveness of the Medan City Directorate in Resolving Labor Disputes - Siburian, Sukses Marhasak Panungkunan; darmawan, Eliana; Pangaribuan, Prengky Bachtiar Hasudungan (JUNCTO: Jurnal Ilmiah Hukum, 2024)
This article or paper aims to analyze the Effectiveness of the Medan City Directorate in Resolving Labor Dispute Problems and Analysis of Obstacles in the Dispute Resolution Process by the Medan Directorate. This study uses an empirical juridical method with a descriptive analysis approach to examine the application of law by the Medan City Directorate in resolving labor disputes, using data from literature studies, field surveys, and interviews with related parties and authorities of the Medan City Manpower Office, namely Mr. Marisi Sinaga, as the Head of PSP or the Head of Disputes, Working Conditions and Wages at the Medan City Manpower Office. Qualitative analysis is applied to evaluate the effectiveness of the Directorate, identify obstacles, and provide recommendations for improvement. The results of the study show that the Medan City Directorate plays an important role in resolving labor disputes through a non-litigation approach, supported by innovations such as Siduta that improve accessibility and service efficiency. Despite facing obstacles such as incomplete documents, geographical distance, and mediator workload, efforts such as socialization, training, and internal capacity building can support more effective and harmonious dispute resolution.